2020
DOI: 10.4014/jmb.2003.03047
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Low-Quality Soil Microbial Community Structure and Activities to Application of a Mixed Material of Humic Acid, Biochar, and Super Absorbent Polymer

Abstract: Low-quality soil with little human disturbance is used in mine soil reclamation in China, such as in deep tillage and soil replacement operations [1]. However, it has extreme texture with high density, low porosity, low water capacity, and poor fertilizer conservation [2]. The low-quality of guest soil is closely related to soil microbial diversity and activity [3, 4]. In recent years, more attention has been paid to the use of organic materials like humic acid, biochar, and super absorbent polymer for mine so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The purpose of soil reclamation in coal mining subsidence area is to reconstruct productive, healthy and sustainable ecosystem of land use after mining. Increasing soil nutrients and enriching microbial population through fertilization is an effective method for ecological restoration in mining areas ( Mummey et al, 2002 ; Cao et al, 2020 ; Li et al, 2020 ; Yan et al, 2021 ). In our study, soil nutrient and bacterial community diversity increased significantly after 4 years of reclamation.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of soil reclamation in coal mining subsidence area is to reconstruct productive, healthy and sustainable ecosystem of land use after mining. Increasing soil nutrients and enriching microbial population through fertilization is an effective method for ecological restoration in mining areas ( Mummey et al, 2002 ; Cao et al, 2020 ; Li et al, 2020 ; Yan et al, 2021 ). In our study, soil nutrient and bacterial community diversity increased significantly after 4 years of reclamation.…”
Section: Discussionmentioning
confidence: 99%
“…Since in these groups, there were also control samples without the use of SarB from their experiment it follows that the addition of either a peat substrate or maize straw than a SarB had a greater impact on bacterial diversity. Li et al (2020) detected that SaP (containing linear anionic polyacrylamide + humic acid + biochar), nine mixtures of different concentrations, affected soil bacterial communities. From the cluster analysis of the bacterial community composition at the OtU level, they found that the control samples showed the greatest similarity with treatments e1 (0.5 g/kg SaP + 3 g/kg humic acid + 5 g/kg biochar) and e5 (1 g/kg SaP + 6 g/kg humic acid + 5 g/kg biochar).…”
Section: Plant Emergencementioning
confidence: 99%
“…Humic compounds offer a range of benefits, including enhanced biological activity, nutrient availability, cation exchange capacity, pH buffering, carbon sequestration, and soil-water relations [37][38][39][40]. Their capacity to promote plant stress tolerance by influencing hormonelike effects and micro-organism activity has also been noted [41][42][43].…”
Section: Introductionmentioning
confidence: 99%